2011
DOI: 10.3389/fpsyg.2011.00082
|View full text |Cite
|
Sign up to set email alerts
|

Trial-by-Trial Variations in Subjective Attentional State are Reflected in Ongoing Prestimulus EEG Alpha Oscillations

Abstract: Parieto-occipital electroencephalogram (EEG) alpha power and subjective reports of attentional state are both associated with visual attention and awareness, but little is currently known about the relationship between these two measures. Here, we bring together these two literatures to explore the relationship between alpha activity and participants’ introspective judgments of attentional state as each varied from trial-to-trial during performance of a visual detection task. We collected participants’ subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
136
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(164 citation statements)
references
References 87 publications
15
136
3
Order By: Relevance
“…(Aue et al, 2009)), we can hope to identify brain activity which reflect this variation. Indeed it has been found that ongoing pre-stimulus alpha power modulates perception performance (see (Jensen and Mazaheri, 2010) for a review), and is negatively correlated with subjective attentional state (Macdonald et al, 2011). Recent studies also demonstrate increased alpha band activity up to 20 resp.…”
Section: Experimental Results On Real Eeg Datamentioning
confidence: 96%
“…(Aue et al, 2009)), we can hope to identify brain activity which reflect this variation. Indeed it has been found that ongoing pre-stimulus alpha power modulates perception performance (see (Jensen and Mazaheri, 2010) for a review), and is negatively correlated with subjective attentional state (Macdonald et al, 2011). Recent studies also demonstrate increased alpha band activity up to 20 resp.…”
Section: Experimental Results On Real Eeg Datamentioning
confidence: 96%
“…This approach allows estimation of the contribution of individual frequencies to the analysed signal ( Figure IB). In the case of cognitive electrophysiological research, frequencies are divided into spectral bands with distinct functional associations: delta (1-4 Hz), theta (4-8 Hz), alpha (8)(9)(10)(11)(12)(13)(14), beta (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (>30 Hz) ( Figure IC).…”
Section: Supervisory Systems Of Sustained Attentionmentioning
confidence: 99%
“…It is commonly studied using tasks that require subjects to monitor infrequent and temporally unpredictable signals over extended periods of time (i.e., more than 10 minutes) [7,8]. Changes in sustained attention are measured as both fluctuations [9,10] and deteriorations [7,11] in performance on these tasks. These different measures of performance have been suggested to reflect dissociable cognitive processes [12].…”
Section: Supervisory Systems Of Sustained Attentionmentioning
confidence: 99%
“…Practically, neural measures of user state might prove useful in brain-computer interfaces to flag periods of reduced motivation or attentional focus in which missed targets or false alarms would be more likely (Grier, et al, 2003;Mathan et al, 2006a). Indeed, recent evidence has highlighted neural markers that directly correlate with trial-to-trial variations in participants' self-reported attentional state (Macdonald et al, 2011). The present study utilized similar single-trial analysis techniques (Parra et al, 2002) to assess the potential utility of both ERP and oscillatory EEG activity in assessing participants' motivation on single trials.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, reduced pre-stimulus alpha activity has been shown to be predictive of conscious visual perception in near-threshold detection tasks. For example, decreased alpha activity in the period prior to stimulus onset is associated with improved detection of briefly flashed light stimuli (Ergenoglu et al, 2004), variations in pre-stimulus alpha correlate with subjective ratings of attentional state (Macdonald et al, 2011), and participants with decreased pre-stimulus alpha tend to perform better at detection of backward masked near-threshold stimuli (Hanslmayr et al, 2005). Moreover, phase coupling of pre-stimulus alpha power across scalp electrodes has been shown to be an effective predictor of subsequent correct performance at the level of individual trials with such tasks (Hanslmayr et al, 2007).…”
Section: Introductionmentioning
confidence: 99%